2020
DOI: 10.3390/vetsci7030099
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and National Surveillance System for Foot and Mouth Disease in Cattle in Thailand during 2008–2019

Abstract: Foot and mouth disease (FMD) is a prominent transboundary disease that threatens livestock production and can disrupt the trade in animals and animal products at both regional and international levels. The aims of this study were: (1) to analyze the distribution of FMD in Thailand during the period of 2008 to 2019, (2) to outline a national surveillance approach, and (3) to identify the existing knowledge gap that is associated with this disease in relation to cattle production. We analyzed FMD outbreak data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…One of the main limitations to eradicating FMD is the lack of quality vaccines that boost the immune system of the animal against clinical signs and prevent infection [ 26 ]. The importance of vaccination against FMDV was highlighted by Domingo, Baranowski [ 27 ], Carrillo, Wigdorovitz [ 28 ], who reported that vaccinating all susceptible animals against FMDV with the inactivated virus had been very successful in controlling and preventing the disease in different countries and regions of the world, including Thailand [ 29 ] and Europe [ 30 ]. It is considered that the best method for the control and future eradication of FMD in herds within the study area is the implementation of emergency vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main limitations to eradicating FMD is the lack of quality vaccines that boost the immune system of the animal against clinical signs and prevent infection [ 26 ]. The importance of vaccination against FMDV was highlighted by Domingo, Baranowski [ 27 ], Carrillo, Wigdorovitz [ 28 ], who reported that vaccinating all susceptible animals against FMDV with the inactivated virus had been very successful in controlling and preventing the disease in different countries and regions of the world, including Thailand [ 29 ] and Europe [ 30 ]. It is considered that the best method for the control and future eradication of FMD in herds within the study area is the implementation of emergency vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of FMD in cattle include pyrexia and anorexia, and decreased milk output in dairy animals for 2-3 days [18]. Vesicles form also on the mouth and nasal mucous membrane and on the coronary band between the claws [19]. The result is lip snapping, bruxism, blowjob, lameness, stamping or kicking of feet.…”
Section: Clinical Signs Of Foot Mouth Diseasementioning
confidence: 99%
“…The problems include secondary infections of injuries, decreased milk supply, loss of weight, tongue erosions, hoof distortions, abortion and mastitis. Young animals may nevertheless succeed in myocarditis (figure 5) [18][19][20].…”
Section: Clinical Signs Of Foot Mouth Diseasementioning
confidence: 99%
“…Between 2007 and 2017, 968 FMD outbreaks were reported in Thailand, especially between 2015 and 2016, when outbreak reports peaked at 183 ( 4 ). The FMD prevention strategies in Thailand include routine vaccination programs in ruminants two times per year, or up to three times per year in areas with regular FMD outbreaks ( 12 ). The government supports vaccination by providing free locally produced trivalent FMD vaccines (O, A, and Asia1 strains).…”
Section: Introductionmentioning
confidence: 99%
“…Even though Thailand has been regularly affected by FMD, only a few epidemiological and economic assessment studies were conducted. The previous studies mostly focused on the area level rather than the farm level ( 12 , 13 ). The knowledge gap of FMD impacts at the farm level in Thailand exists.…”
Section: Introductionmentioning
confidence: 99%